Evaluation the Hematological Alterations in Females with Breast Cancer (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Cross-sectional research conducted in Baghdad province, women with breast cancer, both young and elderly, were evaluated alongside healthy persons to determine certain hematological parameters. This study aimed for evaluation the Hematological alterations in females with breast cancer.   Materials and Methods: The investigation was conducted in private hospitals, forty women diagnosed with breast cancer and ten healthy controls were randomly sampled between 2020 and 2022. From each female patient and control , three milliliters of venous blood were given, which was then dispensed into an EDTA container, in order to evaluate the hematological parameters. Additional analyses utilizing the (Auto Hematology Analyzer) were carried out on the EDTA samples, including PCV, WBC, RBC, platelet count, and lymphocyte count. Procedures followed in the handbook for the testing. Using the conventional Westergren technique, the ESR was calculated.  Results: The current results showed that there was a significant difference between the examined population and the control group in terms of mean RBC, PCV, platelets count, WBC, and lymphocytes, with a p-value of less than 0.05. In contrast, the control participants had considerably lower mean ESR levels (p < 0.05) compared to the breast cancer patients.Conclusion:  breast cancer can affect all blood components including RBC, WBC, platelets and its related parameters.